2019
DOI: 10.4401/ag-7617
|View full text |Cite
|
Sign up to set email alerts
|

The source mechanism of the seismic events during the sequence of the moderate-size crustal earthquake of November 22, 2014 of Vrancea region (Romania)

Abstract: The moderate-size earthquake (ML 5.7) which occurred on November 22, 2014 in Vrancea region (Romania), is the largest crustal event instrumentally recorded. Its aftershock sequence lasted around 70 days, 222 earthquakes with M L ≥ 0.1 being located using the records collected by the Romanian seismic network. The seismic sequence occurred mainly in the lower crust (depths greater than 25 km), and the epicenter distribution-along a NNE-SSW direction-follows the orientation of the Vrancea crustal earthquakes alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…It is worth noticing that for the event that occurred in 12012015, 06:08 (GMT), M L = 4.2, our results indicate a reverse focal mechanism, with the nodal planes NE-SW oriented, which contradicts the normal fault plane solution determined by [32]. We assume that the fault mechanism determined by the above study is flawed due to the event location, which in their study is reported as being located ~40 km towards the north, and at a greater depth (with ~20 km) as compared to the location provided by the ROMPLUS catalogue.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…It is worth noticing that for the event that occurred in 12012015, 06:08 (GMT), M L = 4.2, our results indicate a reverse focal mechanism, with the nodal planes NE-SW oriented, which contradicts the normal fault plane solution determined by [32]. We assume that the fault mechanism determined by the above study is flawed due to the event location, which in their study is reported as being located ~40 km towards the north, and at a greater depth (with ~20 km) as compared to the location provided by the ROMPLUS catalogue.…”
Section: Discussioncontrasting
confidence: 84%
“…For the mainshock, the fault plane solution indicates normal faulting with both nodal planes NW-SE oriented, in the direction of the Peceneaga-Camena Fault zone. Our determination shows a good similarity with the solutions computed by several international centers (INGV, USGS, GFZ), as well as with the solution of [32]. The compression axis is plunging almost vertically, while the extension axis is almost horizontal W-E oriented.…”
Section: Focal Mechanismssupporting
confidence: 81%
See 2 more Smart Citations
“…The fault plane solutions are obtained using the FOCMEC code 77 using the velocity model of 7 and integrated in the SEISAN software 78 . These solutions were estimated from P-wave polarities for events with at least 10 records, filtered based on the weight assigned to the P onset (discrete classed from 0, best, to 3, worse) keeping only polarities for picks with weights 0 and 1 and rejecting those with weight 2 and 3, therefore solutions' confidence level is reliable 79 . The location of the seismic stations and seismic events can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%